Archean granulites from Mt.Riiser-Larsen in Enderby Land, East Antarctica - Motoyoshi, Yoichi; Matsueda, Hiroharu (1984)
P(論文) Mt. Riiser-Larsen in Enderby Land, which is a part of the Napier Complex in the East Antarctic Shield, is underlain by the Archean granulites formed under the pyroxene granulite-facies condition. Characteristic mineral associations of sapphirine+quartz, orthopyroxene+sillimanite+quartz and garnet+sillimanite+quartz, all of which are breakdown products after cordierite, have coexisted stably at the peak of metamorphism. The variety of these mineral associations would be largely attributed to the chemical compositions of the rocks, namely the Mg/Fe ratio. On the basis of the phase relations determined experimentally and/or theoretically, and with the use of geothermometers and geobarometers, the P-T conditions at the peak of metamorphism are estimated to have been around 900℃, 8-10kbars. On the other hand, P_<H_2O> must have been considerably lower than P_ , which is suggested by the absence of migmatitic facies and hydrous phases in the mineral assemblages. departmental bulletin paper